MODEL PEMBELAJARAN BERBASIS MASALAH BERBENTUK SOAL CERITA MATEMATIKA TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Nisa Rohmatun Yashiroh; Nurdyansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was conducted on the grounds of students' low critical thinking skills in mathematics. The purpose of this study was to determine the effect of problem-based learning models on students' critical thinking skills. This research was conducted on 20 students at SDN Simoketawang for the 2023/2024 academic year. This research method uses descriptive quantitative methods with purposive sampling data analysis techniques. Researchers used the pre-test and post-test to determine the development and impact of the problem-based learning model style. Data collection techniques in this study used hypothesis testing (t-test) to determine the effect of problem-based learning models in the form of math word problems on mathematical critical thinking. This is reflected in the results of the hypothesis test (t-test) which has a significance value of 0.000 <0.05. Therefore, before and after the treatment there was an increase and had an impact on students' critical thinking skills. Therefore, it can be concluded that the problem-based learning model influences students' critical thinking skills during mathematics learning.